The Effect of Educational Intervention Based on Health Belief Model on Nurses' Stress Management in Intensive Care Units - Nahid Khazar; Zahra Jalili; Leila Nazary manesh (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objectives: Stress is one of the main problems of nurses, which greatly affects their professional performance and their personal life and causes conflict between work and life. The purpose of this research was to identify the effects of Health Belief model-based training on nurses' occupational stress. Materials and Methods: This is a Quasi-experimental study conducted on nurses. 45 nurses were randomly selected from special wards of a hospital as the interventional group and also 42 nurses from another hospital were randomly selected as the control group. Data gathering tool was included the Nursing Stress Scale (NSS) for determining nurses' occupational stress and HBM Model constructs questionnaire to determine the effect of educational intervention. Training program was carried out in three 2-hour sessions. Subjects were monitored for 1 month. Statistical analysis was performed before, and 1 month after training using SPSS software. Statistical tests including Chi- Square, independent t-test, Paired t- test, Kolmogorov- Smirnov were used in this study. Results: Mean NSS score of the intervention group reduced from 107.311 ±20.800 to 89.578 ±23.352 after the training. Moreover, after training, the variables of perceived susceptibility, perceived severity, perceived benefits, cue to action, self-efficacy, and behaviors showed a significant increase and perceived barriers decrease in the intervention group compared to the control group (P < 0.05). Conclusion: Results showed that the Health Belief Model for stress management education was effective in the reduction of nurses' stress level. Considering that behavioral and non-behavioral factors are effective in reducing stress; as a result, to change behavior of individuals, in addition to themselves, it is necessary to pay attention to the environment surrounding them and others influencing their behavior.